100 ideas that changed the web - Boulton, Jim (London : Laurence King Publishing, 2014)
This innovative title looks at the history of the Web from its early roots in the research projects of the US government to the interactive online world we know and use today. Fully illustrated with images of early computing equipment and the inside story of the online world's movers and shakers, the book explains the origins of the Web's key technologies, such as hypertext and mark-up language, the social ideas that underlie its networks, such as open source, and creative commons, and key moments in its development, such as the movement to broadband and the Dotcom Crash. Later ideas look at the origins of social networking and the latest developments on the Web, such as The Cloud and the Semantic Web. Following the design of the previous titles in the series, this book will be in a new, smaller format. It provides an informed and fascinating illustrated history of our most used and fastest-developing technology.
The mundaneum -- The space race -- Hypertext -- The modem -- Graphical user interface -- The mouse -- Markup language -- Xanadu -- The personal computer -- The internet -- Internet service provider -- Bulletin board systems -- Hackers -- Cyberpunk -- Internet protocol suite -- Desktop publishing -- Hypercard -- Graphics interchange format -- The emoticon -- The domain name system -- The project -- Web browser -- The cookie -- The JPEG -- Pornography -- Search -- WiFi -- Open source -- Netiquette -- Apache web server -- Content management systems -- Web analytics -- Massively multi-player online gaming -- Webcam -- Web standards -- Geocities -- The banner ad -- Web auction -- User-centred design -- Net art -- Digital fragility -- Information architecture -- Web chat -- Cascading style sheets -- Metadata -- The webby awards -- Pay per click -- Web mapping -- Blogging -- Scaleable vector graphics -- Webmail -- Viral content -- Internet meme -- The digital wallet -- Ecommerce -- Collaborative filtering -- The drudge report -- RSS feeds -- Web streaming -- The independence of cyberspace -- The Blair witch project -- Peer-to-peer -- Broadband -- Creative commons -- The dot-com bubble -- Web TV -- The wiki -- Infographics -- Augmented reality -- Captcha -- Photo sharing -- Podcast -- The long tail -- AJAX -- Social networking -- Folksonomies -- Perpetual beta -- Online dating -- Surrogate travel -- Casual gaming -- Mashup -- YouTube -- Microblogging -- The QR code -- Real-time reporting -- The mobile web -- User-generated content -- Aggregation -- The app store -- Crowdsourcing -- Gamification -- Open architecture -- Geolocation -- The internet election -- The cloud -- Embeddable fonts -- Tablet devices -- Responsive web design -- Big data -- The semantic web.
Includes bibliographical references (p. 208-209) and index.
Keywords: Internet -- History; World Wide Web; World Wide Web -- History